Implementation of Physical Education, Sports and Health in Nias Regency, North Sumatra - Candra Zebua; Mugiyo Hartono; Hermawan Pamot Raharjo (Universitas Negeri Semarang, 2026)
This study aims to analyze the Physical Education, Sports, and Health (PE) policy at the Junior High School level in Nias Regency, North Sumatra, using Stephen J. Ball's educational policy analysis theory, which encompasses three main contexts: the context of influence, the context of formulation, and the context of implementation. This study uses a qualitative approach with a case study method, through data collection techniques in the form of interviews, observations, and documentation involving elements of the Nias Regency Education Office, school principals, PE teachers, and relevant policy documents. The results show that policy formulation is still influenced by limited coordination and data support. Implementation is running quite well but is hampered by sports facilities, teacher competence, and health facilities in schools. Supporting factors include school commitment, student enthusiasm, and support for the national curriculum; while inhibiting factors include minimal budget, lack of infrastructure, and slow bureaucracy. This study recommends increasing funding, teacher training, and strengthening coordination between stakeholders to optimize PE policy in Nias Regency. In conclusion, the physical education policy in Nias Regency has been implemented but has not been optimal, so it is necessary to increase funding, strengthen teacher competency, and coordinate between stakeholders to optimize its implementation.